2008
DOI: 10.1007/s00259-008-0886-y
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative cerebrovascular reactivity to acetazolamide measured by brain perfusion SPECT predicts development of cerebral ischemic lesions caused by microemboli during carotid endarterectomy

Abstract: Preoperative CVR to acetazolamide measured by quantitative brain perfusion SPECT predicts development of cerebral ischemic lesions on postoperative DWI that are caused by microemboli during CEA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 29 publications
2
26
1
1
Order By: Relevance
“…Variables with a P value of less than 0.2 in the univariate analyses were selected for analysis in the final model. However, preoperative CVR in the affected hemisphere was not adopted in the model because previous studies have already established the strong relationship between this factor and the development of new postoperative cerebral ischemic events or post-CEA hyperperfusion (19,20,(22)(23)(24). Differences were deemed statistically significant if the P value was less than 0.05.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Variables with a P value of less than 0.2 in the univariate analyses were selected for analysis in the final model. However, preoperative CVR in the affected hemisphere was not adopted in the model because previous studies have already established the strong relationship between this factor and the development of new postoperative cerebral ischemic events or post-CEA hyperperfusion (19,20,(22)(23)(24). Differences were deemed statistically significant if the P value was less than 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…According to the concept proposed by Caplan and Hennerici (40), preexisting hemodynamic impairment may facilitate the onset of ischemia due to emboli generated from a proximal lesion. One study has demonstrated that reduction of preoperative cerebrovascular reactivity to acetazolamide measured by brain perfusion SPECT predicts the development of new postoperative cerebral ischemic lesions on DWI that are caused by microemboli generated during carotid dissection in CEA (20).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations